Peningkatan Penguasaan Huruf Hiragana dan Katakana pada Siswa Kelas XI IBB di SMA Negeri 1 Singaraja Berbantuan Media Aplikasi Memory Hint dan Obenkyo - Ida Ayu Putu Aryasti Purnamasari; Ni Nengah Suartini; Desak Made Sri Mardani (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This research aims to improve the mastery of Hiragana and Katakana letters in class XI IBB students at SMA Negeri 1 Singaraja with the help of the Memory Hint and Obenkyo application media. The subjects of this research were 33 students of class XI Language and Culture (IBB) at SMA Negeri 1 Singaraja. Data was collected through observation, tests and interviews. Research data were analyzed qualitatively and quantitatively. The results of this study indicate that learning assisted by the Memory Hint and Obenkyo applications can improve the mastery of Hiragana and Katakana letters. On the results of the Pre-test students obtained an average of 72.2 with a classical completeness of 51.5%. Cycle I obtained an average of 75.6 with a classical completeness of 72.7%. Cycle II get an average of 85.0 with 100% classical completeness. The response of class XI IBB students was classified as positive by showing an increase in learning outcomes and competence achievements. An increase in learning outcomes is indicated by an increase in the achievement score of the Minimum Completeness Criteria, an increase in competence as indicated by the mastery of Hiragana and Katakana letters, as well as an increase in student activity in participating in learning process. Based on these results it can be concluded that learning letters assisted by the Memory Hint and Obenkyo application media is able to improve the mastery of Hiragana and Katakana letters for class XI IBB students.